Safety and Efficacy of Early Endotherapy in Management of Pancreatic Ascites: Western Indian Experience. - Gattani, Mayur G.; Chauhan, Shamshersingh G.; Sethiya, Pratik R.; Chandak, Pooja C.; Lad, Saiprasad G.; Singh, Gaurav K.; Kolhe, Kailash M.; Khairnar, Harshad B.; Pandey, Vikas R.; Ingle, Meghraj A. (Journal of Digestive Endoscopy, 2021)
Background Pancreatic ascites is rare but a known complication of pancreatitis. We aimed to study the timings, safety, and efficacy of therapeutic approaches in its management and the outcomes.Methods We retrospectively studied patients with pancreatic ascites managed in the past 5 years at a single tertiary care center. Therapeutic approaches included conservative therapy, early endoscopic therapy, and surgery. We used descriptive statistics to summarize characteristics of the study population, and performed univariate and binary logistic regression analyses to compare treatment outcomes.Results Of the 125 patients screened, 70 (male, 81.4%) were included. Disruption in the pancreatic duct (PD) was seen in 51.4% of patients on magnetic resonance cholangiopancreatography (MRCP) and 73.3% of patients on endoscopic retrograde cholangiopancreatography (ERCP). The PD in the body region (46.7%) was the most frequent site of disruption. Early endotherapy included a stent bridging the disruption site in 63.3% of patients and sphincterotomy in 76.7% of patients with a median time to ERCP from symptom onset being 8.5 days. The success rate in early endotherapy was 81.7%, while the recurrence rate was 8%. For conservative therapy only, the success rate was 60% with recurrence in two-thirds. The variables crucial in the success of endotherapy were a partial disruption (p < 0.001), ductal disruption site (p = 0.004), sphincterotomy (p = 0.013), and a bridging stent (p = 0.001). Significant pancreatic necrosis (p < 0.001) and intraductal calculi (p = 0.002) were the factors responsible for failure in endotherapy.Conclusions Early endotherapy is safe and effective in the treatment of pancreatic ascites. The efficacy of endotherapy is augmented by PD stenting combined with pancreatic sphincterotomy and a bridging stent.
Keywords: cholangiopancreatography; endoscopic retrograde; Magnetic resonance; ascites; pancreatitis; acute necrotizing; sphincterotomy